A fingerprinting metabolomic approach reveals deregulation of endogenous metabolites after the intake of a bioactive garlic supplement. (October 2018) - Fernández-Ochoa, Álvaro; Borrás-Linares, Isabel; Baños, Alberto; García-López, J. David; Guillamón, Enrique; Nuñez-Lechado, Cristina; Quirantes-Piné, Rosa; Segura-Carretero, Antonio
Graphical abstract: Highlights: A dietary intervention assay was performed with a bioactive garlic food supplement. The concentrations of LysoPC, LysoPE and acylcarnitines increased after the intake. The decrease of fructosamines was detected after the supplement intake. The bioactive garlic food supplement altered mainly the phospholipid metabolism. The observed changes may be related to the antioxidant and antiglycation properties. Abstract: Garlic (Allium sativum) has been described as containing phytonutrients with healthy properties. In this study, the effect of a bioactive garlic food supplement intake on human plasma metabolome was examined with the aim of understanding the mechanisms of action and involved pathways responsible for beneficial effects. With this purpose, a dietary intervention assay was performed in thirty healthy volunteers collecting plasma samples before intake and after one month of daily supplement consumption. Plasma samples were analysed by a fingerprinting metabolomic strategy based on HPLC-ESI-QTOF-MS. Our results revealed a total of 26 metabolites affected by supplement intake. In general, alterations in phospholipid metabolism were shown, detecting an increase in lysophosphatidylcholines, lysophosphatidylethanolamines and acylcarnitines. It is also remarkable that the level of four fructosamines decreased after the assay. These results are according with the antioxidant and antiglycation properties that have been previously associated with garlic extracts.